1995
DOI: 10.1200/jco.1995.13.11.2731
|View full text |Cite
|
Sign up to set email alerts
|

Advanced breast cancer: a phase II trial with gemcitabine.

Abstract: In view of the single-agent activity seen in advanced breast cancer, modest toxicity profile, and novel mechanism of action, gemcitabine deserves evaluation in breast cancer and is an ideal candidate for combination therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
117
0
2

Year Published

1996
1996
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(120 citation statements)
references
References 18 publications
1
117
0
2
Order By: Relevance
“…Gemcitabine undergoes intracellular phosphorylation to the active metabolites gemcitabine diphosphate and gemcitabine triphosphate, leading to inhibition of ribonucleotide reductase and incorporation of gemcitabine triphosphate into DNA and RNA (Xu and Plunkett, 1992;Ruiz van Haperen et al, 1993). It is active against non-small-cell lung cancer, pancreatic cancer, breast cancer and ovarian cancer (Abratt et al, 1994;Lund et al, 1994;Carmichael et al, 1995Carmichael et al, , 1996. A review of gemcitabine safety profile establishes this drug as a relatively safe antimetabolite, with adverse events that generally are manageable and reversible, rarely leading to discontinuation of the drug.…”
mentioning
confidence: 99%
“…Gemcitabine undergoes intracellular phosphorylation to the active metabolites gemcitabine diphosphate and gemcitabine triphosphate, leading to inhibition of ribonucleotide reductase and incorporation of gemcitabine triphosphate into DNA and RNA (Xu and Plunkett, 1992;Ruiz van Haperen et al, 1993). It is active against non-small-cell lung cancer, pancreatic cancer, breast cancer and ovarian cancer (Abratt et al, 1994;Lund et al, 1994;Carmichael et al, 1995Carmichael et al, , 1996. A review of gemcitabine safety profile establishes this drug as a relatively safe antimetabolite, with adverse events that generally are manageable and reversible, rarely leading to discontinuation of the drug.…”
mentioning
confidence: 99%
“…However, we would claim this is often the case. For example, in the recent literature there are three related Phase II trials of single agent gemcitabine in breast cancer -related in the sense of both overlapping authorship and type of disease (metastatic and/or advanced) (Carmichael et al, 1995;Possinger et al, 1999;Schmid et al, 1999). However, the methodology is equally applicable if the (down-weighted) prior had been obtained from information external to the investigating teamperhaps from the newly available literature.…”
Section: Clinicalmentioning
confidence: 99%
“…Preclinical studies have indicated that, unlike cytarabine, gemcitabine had a high level of activity in solid tumours, and this has been borne out in clinical trials. Activity has been seen for this agent in a variety of tumours, including pancreas, ovary, bladder, breast and lung cancers (Kaye, 1994;Abratt et al, 1995;Anderson et al, 1995;Carmichael et al, 1995;Burris et al, 1997). Improvements have been seen in the quality of life of patients with pancreatic cancer and other trials have investigated the effect of gemcitabine in combination therapy, for example with cisplatin in the treatment of NSCLC (Steward, 1997).…”
Section: Nucleoside Analoguesmentioning
confidence: 99%